A New Model to Produce Sagittal Plane Rotational Induced Diffuse Axonal Injuries - Davidsson, Johan; Risling, Marten (Frontiers in Neurology, 2011)
A new in vivo animal model that produces diffuse brain injuries (DBI) in sagittal plane rearward rotational acceleration has been developed. In this model, the skull of an anesthetized adult rat is tightly secured to a rotating bar. During trauma, the bar is impacted by a striker that causes the bar and the animal head to rotate rearward; the acceleration phase last 0.4 ms and is followed by a rotation at constant speed and a gentle deceleration when the bar makes contact with a padded stop. The total head angle change is less than 30 degrees. By adjusting the air pressure in the rifle used to accelerate the striker, resulting rotational acceleration between 0.3 and 2.1 Mrad/s2 can be produced. Numerous combinations of trauma levels, post-trauma survival times, brain and serum retrieval and tissue preparation techniques were adopted to characterise this new model. The trauma caused subdural bleedings in animals exposed to severe trauma. Staining brain tissue with β-Amyloid Precursor Protein antibodies and FD Neurosilver that detect degenerating axons revealed wide spread axonal injuries (AI) in the corpus callosum, the border between the corpus callosum and cortex and in tracts in the brain stem. The observed AI:s were apparent only when the rotational acceleration level was moderate and above. On the contrary, only limited signs of contusion injuries were observed following trauma. S100 serum analyses indicate that blood vessel and glia cell injuries occur following moderate levels of trauma despite the absence of obvious BBB injuries. We conclude that this rotational trauma model is capable of producing graded axonal injury, is repeatable and produces limited other types of traumatic brain injuries (TBI) and as such is useful in the study of injury biomechanics, diagnostics and treatment strategies following diffuse axonal injury (DAI).